2013
DOI: 10.1099/jmm.0.045336-0
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of capillary electrophoresis and direct sequencing in upstream conserved sequence region analysis of Pneumocystis jirovecii strains

Abstract: The MSG is encoded by a multi-copy gene family, with an estimated 80 copies per genome, which are clustered in tandem arrays near the telomeres of each chromosome. Pneumocystis can vary its expressed MSG, presumably as a mechanism to avoid the host immune system (Keely & Stringer, 2009;Cornillot et al., 2002;Keely et al., 2005).The MSG gene is located immediately downstream of a region called the upstream conserved sequence (UCS). The UCS is considered to be essential for the expression of MSG and contains a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The number of repeats can be determined by PCR amplification of the VNTR-containing region followed by high-resolution denaturing gel electrophoresis (300) (Fig. 8) or fluorescence capillary electrophoresis (371). A major benefit of this method is the high sensitivity for detection of a minor population in mixed populations, which can be seen in up to 92% of patients with PCP (see Table S1 in the supplemental material).…”
Section: Epidemiology Of Pneumocystis Methods For Molecular Typingmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of repeats can be determined by PCR amplification of the VNTR-containing region followed by high-resolution denaturing gel electrophoresis (300) (Fig. 8) or fluorescence capillary electrophoresis (371). A major benefit of this method is the high sensitivity for detection of a minor population in mixed populations, which can be seen in up to 92% of patients with PCP (see Table S1 in the supplemental material).…”
Section: Epidemiology Of Pneumocystis Methods For Molecular Typingmentioning
confidence: 99%
“…Isolates with the same number of repeat units can have different distribution patterns of repeat types. Application of this VNTR method to different PCP patient populations worldwide has found that the number of repeat units varies from 2 to 6, with 2, 3, and 4 repeats being the most common (300,319,(371)(372)(373)(374). The 6-repeat allele contains only one repeat pattern, while all other alleles reported, to date, harbor two or more different repeat patterns.…”
Section: Epidemiology Of Pneumocystis Methods For Molecular Typingmentioning
confidence: 99%
“…UCS is known to have a highly variable number of tandem repeats in the intron in P. jirovecii (19,39,40). In this study, we demonstrated for the first time the presence of inter-and intrastrain variations in tandem repeats in the intron of UCSs in P. carinii and P. oryctolagi.…”
Section: Figmentioning
confidence: 51%
“…UCS is known to have a highly variable number of tandem repeats in the intron in P. jirovecii (20, 39, 40). In this study, we demonstrated for the first time the presence of inter- and intra-strain variations in tandem repeats in the intron of UCS in P. carinii and P. oryctolagi.…”
Section: Discussionmentioning
confidence: 99%